The impact of demographic factors toward customer loyalty: A study on credit card users / Ramli Saad...[et al.] - Saad, Ramli; Ishak, Hadzli; Johari, Nur Rashidi (2010)
In today competitive, complex and dynamic environment of the banking industry, the very slight differences which exist in financial services and products together with an increasingly demanding customer have led to a great transformation in the industry. The traditional productoriented bank is becoming increasingly customer-oriented in accordance with the basic principles of relational marketing, which focuses on customer loyalty as its main goal (Gilmore,1997). Thus, the purpose of this paper is to empirically examine the extent to which demographics correlate with service loyalty focusing on credit card service. According to Naresh K. Malhotra (2003), convenience sampling attempts to obtain a sample of convenience elements. Taking this into consideration, sample of 200 respondents were randomly chosen in this survey which 150 respondents gave the feedback. Correlation Pearson test being used to determine the relationship between demographic factors (age, gender, income lc\·el, occupation and li!estylc) and customer loyalty. The result from hypotheses testing has shown that only income level having positive relationship with customer loyalty as compared to other four demographic factors. The evidence behind this statement is because of the value or r achieved in Pearson Correlation Test. The value or r for income factor was 0.223 while for the occupation factor; the r-value was result -0.163 and the rest age, gender and lifestyle do not influence much in the area of study. Thus, this finding is in line with what has been found by East (1995) indicated that shoppers who are more concerned about prices are less loyal, with high income groups being more loyal than low income groups.